Annual volume of the laws of the Federal Republic of Nigeria : containing decrees and subsidiary legislation - Nigeria (Lagos : Federal Ministry of Information, 1968)
The book is the Annual volume of the laws of the Federal Republic of Nigeria containing decrees and subsidiary legislation of 1968-
Publisher varies, 1978-<1979>: Federal Govt. Press.
gp. 22/01/2019
Loans
Keywords: Session laws; Session laws; Nigeria